2019
DOI: 10.3390/nu11122865
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral Nutrition in Patients with Inflammatory Bowel Disease Systematic Review, Meta-Analysis and Meta-Regression

Abstract: Inflammatory bowel disease (IBD) is a chronic disease mediated by the immune system and characterized by the inflammation of the gastrointestinal tract. This study is to understand how the use of parenteral nutrition (PN) can affect the adult population diagnosed with IBD. We conducted a systematic review, meta-analysis, and meta-regression. From the different databases (MEDLINE, Scopus, Cochrane, LILACS, CINAHL, WOS), we found 119 registers with an accuracy of 16% (19 registers). After a full-text review, onl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 65 publications
0
8
0
Order By: Relevance
“…This study examined quality‐of‐life metrics in patients receiving home PN and found the scores comparable to those of patients on chronic hemodialysis 31 . Finally, a recent meta‐analysis has also demonstrated that home PN is associated with improved markers of disease activity and nutrition status in IBD patients, including CRP, serum albumin level, and Crohn's Disease Activity Index 32 …”
Section: Discussionmentioning
confidence: 77%
“…This study examined quality‐of‐life metrics in patients receiving home PN and found the scores comparable to those of patients on chronic hemodialysis 31 . Finally, a recent meta‐analysis has also demonstrated that home PN is associated with improved markers of disease activity and nutrition status in IBD patients, including CRP, serum albumin level, and Crohn's Disease Activity Index 32 …”
Section: Discussionmentioning
confidence: 77%
“…A number of studies have been conducted to identify the risk factors for patients with CD undergoing surgery. Several risk factors, such as age, hypoalbuminemia, and anemia, are associated with postoperative outcomes [8][9][10][11]. However, the role of sarcopenia was not described well in these studies.…”
Section: Introductionmentioning
confidence: 93%
“…The PC does not change after the intervention. COM using NP was observed, although the proportion is low [16].…”
Section: Vol 16 Iss 1 Year 2023 International Journal Of Nutrologymentioning
confidence: 88%